Disc prolapse in pregnancy - Arya, Sangeeta; Tripathi, Nidhi; Singh, Amrita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Surgery is required only in about 1 in 10 cases of slipped disc. It may be considered if there is evidence of severe nerve compression, symptoms not improved using other treatments, having difficulty in standing or walking, have severe symptoms such as progressive muscle, weakness or altered bladder function. A microdiscectomy is typically performed for a herniated lumbar disc and is actually more effective for treating leg pain (also known as radiculopathy) than lower back pain. Impingement on the nerve root (compression) can cause substantial leg pain. While it may take weeks or months for the nerve root to fully heal and any numbness or weakness to get better, patients normally feel relief from leg pain almost immediately after a microdiscectomy spine surgery. Backache during pregnancy must not be overlooked as only minor ailment due to mechanical stress. Patient should be investigated on lines of spinal pathology.